Smart Textiles Production Overview of Materials, Sensor and Production Technologies for Industrial Smart Textiles - Gehrke, Inga (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The research field of smart textiles is currently witnessing a rapidly growing number of applications integrating intelligent functions in textile substrates. With an increasing amount of new developed product prototypes, the number of materials used and that of specially designed production technologies are also growing. This book is intended to provide an overview of materials, production technologies, and product concepts to different groups concerned with smart textiles. It will help designers to understand the possibilities of smart textile production, so that they are enabled to design this type of products. It will also help textile and electronics manufacturers to understand which production technologies are suitable to meet certain product requirements.